O financiamento dos investimentos sob uma perspectiva keynesiana: uma análise da economia brasileira no período 2008-2014 - Lopes, Luciana Maria de Oliveira (2016)
The discussion on the financing of investment falls within a context in which economists recognize the need and importance of investment for economic growth, but there is between them, a consensus on the conditions under which they must happen, because diverge on the direction of causality savings relative to investment. While neoclassical economists are based on the theory of loan funds, Keynesian economists build their arguments on the principle of effective demand. Faced with this controversy, this thesis first analyze the necessary conditions to obtain the levels of economic growth from the perspective of these two theories, and then once it is established that the obstacle to investment is given by the lack of funding and not by insufficient savings ex-ante will analyze the financing of investments in a Keynesian perspective. Therefore, it is intended with this thesis, analyze from the existing theoretical controversy, one of the possible causes of the difficulties in investing enough to maintain long-term economic growth rates